2022
DOI: 10.3389/fonc.2022.679115
|View full text |Cite|
|
Sign up to set email alerts
|

Comparison of Prognosis Between Microscopically Positive and Negative Surgical Margins for Primary Gastrointestinal Stromal Tumors: A Systematic Review and Meta-Analysis

Abstract: BackgroundThis meta-analysis aimed to determine the prognostic impact of microscopically positive margins (R1) on primary gastrointestinal stromal tumors.MethodsA literature search was performed using PubMed, Embase, Web of Science, and Cochrane Library for studies up to 23 November 2020. The pooled disease-free survival (DFS) and overall survival (OS) between R1 and negative margins (R0) were estimated using a random-effects model.ResultsTwenty studies with 6,465 patients were included. Compared with R0 resec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…A large retrospective study found no significant differences in RFS between R0 and R1 resections 5. Conversely, a recent meta-analysis showed a lower RFS for R1 resections even when combined with adjuvant imatinib 13. While R0 resections remain the ideal outcome, it may not always be possible due to the location of the tumour.…”
Section: Discussionmentioning
confidence: 98%
“…A large retrospective study found no significant differences in RFS between R0 and R1 resections 5. Conversely, a recent meta-analysis showed a lower RFS for R1 resections even when combined with adjuvant imatinib 13. While R0 resections remain the ideal outcome, it may not always be possible due to the location of the tumour.…”
Section: Discussionmentioning
confidence: 98%
“…The pooled results showed that DFS was not significantly associated with neoadjuvant imatinib in rectal GIST. It is reported that positive margin is possibly associated with the recurrence of GIST but this negative impact disappeared in the era of imatinib due to the use of adjuvant imatinib ( Liu et al, 2022 ). This comparable DFS between neoadjuvant imatinib group and no-neoadjuvant therapy group in current meta-analysis might partly due to the balanced rate of R0 resection between the two groups and the proper use of adjuvant imatinib in both groups.…”
Section: Discussionmentioning
confidence: 99%
“…A positive surgical margin (PSM) denotes the presence of residual cancer cells at the margin of resected specimens, and has been shown to increase the risk of local recurrence and decrease overall survival in several cancer types. [1][2][3][4] Numerous studies have further stratified recurrence risk levels based on margin status, with the recommendation of additional therapies if a PSM is present. [5][6][7][8] Accurate identification of PSMs during surgery is, therefore, crucial to guide secondary resection and avoid the need for reoperations or adjuvant treatment.…”
Section: Introductionmentioning
confidence: 99%